2015
DOI: 10.1111/jicd.12187
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the shaping ability of two different nickel–titanium rotary files in curved root canals of extracted human molar teeth

Abstract: The ProTaper Universal and ProTaper Next systems performed similarly with regard to the straightening of curved root canals and apical transportation. ProTaper Next was significantly faster than ProTaper Universal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Instruments with different kinematics can be used for root canal preparation . Irrespective of the system used, all promote extrusion of microorganisms, contaminated dentin, irrigant solutions, and remaining pulp tissue beyond the apical foramen, causing postoperative complications, such as periapical inflammation and pain .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instruments with different kinematics can be used for root canal preparation . Irrespective of the system used, all promote extrusion of microorganisms, contaminated dentin, irrigant solutions, and remaining pulp tissue beyond the apical foramen, causing postoperative complications, such as periapical inflammation and pain .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cross‐section and asymmetrical rotation axis of the PTN system instruments, enable them to cut a larger amount of dentin than instruments of the conventional ProTaper Universal (PTU; Dentsply‐Maillefer, Switzerland) and RC systems . Therefore, the combination of distinct characteristics, such as kinematic motion, type of alloy, and cross‐section of the instruments, plays a fundamental role in their shaping ability …”
Section: Introductionmentioning
confidence: 99%
“…Extracted teeth were selected for the present study. Although simulated canals can be better standardized in terms of their root curvature and morphology (Ferrara, Taschieri, Corbella, Ceci, Del Fabbro, & Machtou, ), they cannot simulate the same range of hardness and surface resistance of natural teeth. Therefore, their surface would not be filed similar to a natural root.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety simulated S-shaped root canals in clear resin blocks (Endo Training block-S, Dentsply Maillefer, Ballaigues, Switzerland) with a60 o coronal curvature (5mm radius) and 60 o apical curvature (4mm radius) were used in this study. All canals included the following: 0.02 taper, 16mm length and 0.15mm apical diameter (Pic 1).Sample size calculation before the study revealed a minimum of 15 canals in each group to support the statistical analysis (Ferrara G, 2017). The blocks were randomly assigned into three groups (n = 30), according to the investigated instruments: Hyflex® CM (CM group), Protaper GOLD TM (GOLD group), and Twisted File® (R group).…”
Section: Methodsmentioning
confidence: 99%
“…Although the manufacturers declare that their production is very resistant and long-lasting, there is still no standardized method for testing and improving this. Extracted human teeth are ideal material for testing, but neither hardness of dentine nor curves of canal anatomy can be standardized (Ferrara G, 2017). The previous studies have shown that mistakes and complications during mechanical root canal instrumentation depend on characteristics of the instruments' alloy (Hiran-us S P. S., 2016, Hiran-us S S. J., 2005, Gergi R, 2010, Gutmann JL, 2012.…”
Section: Introductionmentioning
confidence: 99%